(3ejRGf GdebGOjQs - (3GdCUagGfj, GdeLdSj, eMeO HGbQ Hf eMeO Jbj Hf ebUhO GdCUagGfj, J (B1111(3g` (B1700(3es ((3GdeTgO GdMSjfjs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdPj GQJaY Yf eWGQM GdCagGe, adG JhRf UaGJ YXeJg (B... (3Ef cKjQG ef GdeSGFd GdTQYjI eHfj Ydi eYQaI GdCbOGQ hde CLO CMO ef YdeGFfG MbbgG Ydi hLg JQJaY Yf QLhYgG GdCSJGQs
(3BNQgG (B:s
(3BNQgG(B: (3hCfgG LRA ef CQHYjf LRA ef GdfUGH hGdjHYI ef gPg GdaOQGge jSGhj QHY YTQ GdeCJjf ef OQGge Ref GdQShd aYdehG Cfg jdRe aj GdeCJjf ef KdK GdOQGge SHYI ef gPg GdOQGge hGddg CYde(B.s
(3jdjgG QSGdI aj UjZ YbO GdeJYI (B(12 - 15) (3hdYdgG EMOi QSGFd GdeLdSj GdSHY, jdjgG ahGFO (B(15 - 20)s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 48s
(3GdPQjYI, L (B23: 195s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis